The ultimate betrayal [large type] - Martin, Kat (Martin, Kat. Maximum Security, 2020)
When journalist Jessie Kegan's father is accused of espionage and treason, Jessie has no doubt he is innocent. Before Colonel Kegan can stand trial, he's found dead -- and Jessie suspects it was murder. She's determined to clear her father's name but going after the truth puts her in the cross-hairs of a killer who wants that truth to stay buried with her father. Protecting Jessie Kegan is a job bodyguard Brandon Garrett can't refuse. Jessie isn't just a client at Maximum Security -- she's the sister of his best friend Danny, killed in Afghanistan. Jessie and Bran will have to risk everything to expose her father's killer -- before his legacy dies with his daughter.